A Self-Reported of Malaysian Drivers on High Beam: Frequency, Motivations, and Opinions - M.N.A.M. Norzam; J. Karjanto; N. Md Yusof; M.Z. Hasan; A.F.H. Zulkifli; M.Z. Baharom; Z.M. Jawi; M.S. Solah; G.W.M. Rauterberg (Journal of the Society of Automotive Engineers Malaysia, 2023)
There are various types of Malaysian drivers using the high beam in different situations, such as driving when it is raining or in foggy conditions. This study aims to explore Malaysian drivers using the high beam through a self-reported questionnaire. Also, Malaysian drivers’ concerns, knowledge, and attitudes toward high beams are being investigated. This study is essential to increase Malaysian awareness about the importance of using high beams to reduce road accidents. The data was obtained from 403 respondents of Malaysian drivers of various age ranges through a questionnaire. The results found that 96.3% of the respondents are more concerned about crashing when it is dark than when it is light. Their concerns include lacking visibility due to weather or low lighting and seeing animals on the road. Besides that, most of the respondents use the high beam when driving in streets with little or no street lighting. Furthermore, most respondents stated that it is vital to use high beams, and 85.9% of them agree that automatic high beams highlight an important safety in cars. They said so because the system provides a safety feature since it would prevent glare to the other road users that could cause an accident.